Monitoring Cairan Infus Secara Realtime - Hidayati, Kurnia; Barwaqah, Rico Basyar (Universitas Trilogi, 2018)
At present, many are found in a hospital, the number of inpatients is not balanced with the number of medical staff, especially in the nursing service on duty 24 hours to monitor the patient's condition one by one. As a result of these limitations, the possibility of negligence of the guard officer is very possible, especially in monitoring the condition of infusion fluids in patients. In the task of monitoring the condition of the patient's intravenous fluids, nurses usually have to go back and forth and check the condition of the infusion manually at any time that has been previously estimated. On the basis of this reality, in this final assignment a monitoring system for intravenous fluids was made in real time and centrally that can control the infusion fluid volume of patients based on ATMEGA32 microcontroller with proportional-derivative control method and can provide information about the condition of the patient's actual infusion fluid to medical personnel or guard officers centrally using cables that reconnected and function as a means of communication between the microcontroller and the computer. This tool uses a light sensor to detect the height of the infusion fluid and convert it to liquid volume at ATMEGA 32. If the liquid reaches the minimum volume, then the information from the sensor running or detecting infusion fluid will be processed through a microcontroller and sent to a computer that functions as a monitor or LCD.